The kinetic properties of various R258 mutants of deacetoxycephalosporin C synthase. - Lee, H; Dai, Y; Shiau, C; Schofield, C; Lloyd, MD (2003)
Site-directed mutagenesis was used to investigate the control of 2-oxoacid cosubstrate selectivity by deacetoxycephalosporin C synthase. The wild-type enzyme has a requirement for 2-oxoglutarate and cannot efficiently use hydrophobic 2-oxoacids (e.g. 2-oxohexanoic acid, 2-oxo-4-methyl-pentanoic acid) as the cosubstrate. The following mutant enzymes were produced: R258A, R258L, R258F, R258H and R258K. All of the mutants have broadened cosubstrate selectivity and were able to utilize hydrophobic 2-oxoacids. The efficiency of 2-oxoglutarate utilization by all mutants was decreased as compared to the wild-type enzyme, and in some cases activity was abolished with the natural cosubstrate.